Juvenile Hormone Is an Important Factor in Regulating Aspongopus chinensis Dallas Diapause - Zhou, Wen-Zhen; Wu, You-Fang; Yin, Zhi-Yong; Guo, Jian-Jun; Li, Hai-Yin (Frontiers in Physiology, 2022)
Aspongopuschinensis is a Chinese traditional edible and medicinal insect, which is in great demand in the society. This insect reproduces once a year which is caused by reproductive diapause resulting in insufficient production in wild resources. However, the mechanism of diapause in A. chinensis is still unclear. In this study, we focus on the relationship between juvenile hormones (JHs) and A. chinensis diapause. The results showed that JHIII concentration in diapause adult individuals was significantly lower than that in diapause termination adult individuals. When exogenous JHⅢ was injected into diapause adults, the rate of mating was increased significantly, development of the reproductive systems was accelerated, consumption of fat intensified, the expression of juvenile hormone acid o-methyl-transferase (JHAMT) was upregulated, and juvenile hormone epoxide hydrolase (JHEH) and fatty acid synthase (FAS) gene expressions were downregulated. In addition, RNAi of JHAMT decreased JH concentration, delayed the development of reproductive systems, slowed down fat consumption, and delayed the mean mating occurrence time significantly. Conversely, RNAi of JHEH resulted in an increased concentration of JH, development of reproductive systems was accelerated, consumption of fat was intensified, and mean mating occurrence time advanced significantly. Taken together, these findings uncovered that JH plays an important role in regulating reproductive diapause in A. chinensis and, thus, could provide a theoretical basis for further research on the diapause of A. chinensis.